2019
DOI: 10.3892/ol.2019.10862
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of microRNA‑146a in immune responses and hepatocellular carcinoma (Review)

Abstract: MicroRNAs (miRNAs/miRs), consisting of ~22 nucleotides of single-stranded RNA, participate in post-transcriptional gene regulation by binding to the 3′-untranslated region (UTR) of mRNAs, repressing their translation and promoting their degradation. Studies have shown that certain miRNAs play a key role in the control of various cellular activities, such as inhibiting inflammation, modulating cell differentiation and suppressing cancer growth. The role of miR-146a in the immune response and in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 76 publications
0
30
0
1
Order By: Relevance
“…4,16 3 | miR-146a IN HBV/HCV Hepatitis C virus (HCV) and hepatitis B virus (HBV) infections are the most significant cause of liver fibrosis, cirrhosis, and hepatocellular carcinoma, and have become one of the most harmful viral infectious diseases worldwide. 17 HCV/HBV-associated pathology is principally due to some immunological reasons rather than the HBV/HCV itself. 18,19 Both the viral infection outcome and antiviral treatment efficacy are primarily dependent on viral/host immune factors.…”
Section: Mir-146amentioning
confidence: 99%
“…4,16 3 | miR-146a IN HBV/HCV Hepatitis C virus (HCV) and hepatitis B virus (HBV) infections are the most significant cause of liver fibrosis, cirrhosis, and hepatocellular carcinoma, and have become one of the most harmful viral infectious diseases worldwide. 17 HCV/HBV-associated pathology is principally due to some immunological reasons rather than the HBV/HCV itself. 18,19 Both the viral infection outcome and antiviral treatment efficacy are primarily dependent on viral/host immune factors.…”
Section: Mir-146amentioning
confidence: 99%
“…At present, miRNAs have been increasingly found to have important roles in the development of cancer. it has been shown that miR-146a not only has a tumor-suppressive effect, but also plays a critical role in the growth of HCC cells and that genetic variation of miR-146a may be a risk factor for developing Hcc (21). The expression of mir143HG was significantly downregulated in HCC cells and tissues, and was associated with the staging and prognosis of patients with Hcc (22).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Also, miR-146a has been found function as an oncogene in hepatocellular carcinoma. 14,15 However, the potential mechanism of miR-164a in retinoblastoma still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Recent years, more and more studies have found that miR-146a also act as an oncogene in hepatocellular carcinoma. 14,15 Much attentions have been paid to miRNAs in retinoblastoma, however, the pathological correlation of miR-146a in retinoblastoma was poorly knew. Thus, our study mainly focused on the expression of miR-146a in retinoblastoma and aiming to reveal its potential mechanism.…”
Section: Introductionmentioning
confidence: 99%